THE CHEMICAL COMPOSITION OF HONEY COLLECTED FROM BEES OF DIFFERENT GENOTYPES IN THE FERGHANA VALLEY (Scientific journal of the Fergana State University, 2023)
The article studied and gave an appropriate assessment of the chemical composition of honey collected from bee colonies of different genotypes in the Ferghana Valley in the spring and summer.